USM, TORAY TO FURTHER STRENGTHEN SMART PARTNERSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, September 2016 Universiti Sains Malaysia (USM) and TORAY Group (Malaysia) of Companies (Toray) have agreed to continue to strengthen their smart partnership to further intensify collaborations in research, teaching and learning.